Reproductive Health Care in Adolescents with Vaginal Discharge: A Case Report": Reproductive Health Care in Adolescents with Vaginal Discharge: A Case Report" - Asiva, siti; juariah, juariah; Mulyati, sri (Jurnal Kesehatan Siliwangi, 2024)
Vaginal discharge is a fluid released from the genital area, excluding blood, and often occurs due to poor hygiene in the genital area. Pathological vaginal discharge is characterized by milky white, thick fluid accompanied by itching and is commonly caused by bacterial, viral, fungal, or parasitic infections. Over the past three months, 28 cases of pathological vaginal discharge were reported out of 53 reproductive health complaints at Parung Community Health Center. This report aims to apply midwifery care for Miss R, an 18-year-old patient, with pathological vaginal discharge at Parung Community Health Center.The method used a case report with a SOAP approach (Subjective, Objective, Analysis, Management). Data were collected through interviews, observations, physical examinations, documentation studies, and literature reviews. The analysis showed that Miss R experienced pathological vaginal discharge caused by fungal infection (Candida albicans), triggered by unhealthy habits such as wearing non-absorbent underwear and inadequate genital hygiene.Management included pharmacological therapy with a single dose of oral oral metronidazole 500mg and antifungal cream to relieve itching, as well as non-pharmacological education on genital hygiene, using cotton underwear, and avoiding scented hygiene products. Care was provided over 10 days, resulting in significant improvement in symptoms.In conclusion, the management of pathological vaginal discharge tailored to the patient’s needs produced optimal results. Education for the patient and her family is essential to detect signs of pathological vaginal discharge and prevent recurrence in the future.